Factors contributing to academic cheating among students from Faculty of Business in UiTM Kampus Bandaraya Melaka / Mohammad Faiz Muhd Hijaz - Muhd Hijaz, Mohammad Faiz (Faculty of Business and Management, 2015)
Cheating in academic is one of the unethical behaviors for university student. It is hard to control this kind of problem in the new era of technology and has been one of the critical problems in university. This study is about “factors contributing to academic cheating among students from faculty of business in UITM Kampus Bandaraya Melaka”. Dealing with this kind of problem requires identifying the main causes of the problem. It highlights the background of the study, problem statement, objectives of the study, theoretical framework, research questions, hypothesis of the study, significance of the study, definition of terms, limitations of the study and scope of the study. The purpose of this study is to investigate the level of cheating behavior among business students. Besides that, other purpose is to investigate the relationship between the severities of punishment, peer’s influence and likelihood to be caught and reported. In order to completing this research, the hypothesis was been constructed and focused on the objective to determine whether there has significant relationship between that independent variable and cheating behavior. For this study, final year students from Faculty of Business in UITM Bandaraya Melaka were chosen as respondents. A questionnaire had been distributed to those who involved which are 159 participants. The data was obtained from primary data by using questionnaires. All data collected through the questionnaires were analyzed systematically by Statistical Package for Social Science (SPSS). From the correlation testing, the result shows three independent variables which is severity of punishment; peer’s influence and likelihood to be caught has strong relationship. For multiple regression analysis testing, the results indicate that only severity of punishment have proven that they are the factor that influenced cheating behavior. For hypothesis, it shows that 3 hypothesis which is severity of punishment has relationship and being accepted while the other has being rejected.